Factors Affecting the Upper Limit of the Methotrexate (MTX) CSF Levels Achievable in Children With Brain Tumors Treated With High-dose Intravenous MTX. Issue 7 (October 2016) - Shkalim Zemer, Vered; Toledano, Helen; Ash, Shifra; Cohen, Eytan; Yaniv, Isaac; Cohen, Ian J.
Abstract : Background: Little has been published in the medical literature on serum and cerebrospinal fluid (CSF) methotrexate (MTX) levels in children with brain tumors. Methods: Matched 24-hour serum and CSF MTX levels were studied after 113 treatments in 35 brain tumors patients. Results: A correlation between the 24-hour serum levels of MTX and MTX dosage was observed after 113 treatments in all 35 patients ( r =0.39, P <0.001) but no statistical difference was found between CSF MTX levels in the irradiated and nonirradiated groups ( P =0.12). Nonirradiated children received a lower dose of MTX (12.3±4.8 cf 14.8±3.7) ( P =0.002). The 24-hour MTX CSF levels of these 2 groups were also found to be different (the nonirradiated group 7.6±9.8 cf 12.5±0.15.3). Using the Levene test for variances we found that these variances were not equal and therefore we used the Welch test which resulted in a P -value of 0.04. However, when an analysis of covariance was performed looking at evidence of CSF disease and MTX dose the radiation difference was no longer significant ( P =0.15). The 24-hour CSF MTX levels in children without evidence of active CSF disease were consistently lower than those with active disease using a mixed-model analysis ( P =0.002). Although a 24-hour CSF MTX level of at least 1 μM was observed after infusions of >5 g/m 2 MTX in previously irradiated children and after infusion of ≥10 g/m 2 in nonirradiated children this difference did not reach statistical significance. CSF MTX levels plateau at doses of MTX 15 g/m 2 putting in doubt the value of administering even higher doses of MTX. Conclusions: The 24-hour MTX CSF levels are higher in patients with active CSF disease. Doses of <10 gm/m 2 in children with brain tumors may not achieve a guaranteed 24-hour MTX CSF level of 1 μM. There may be little value in a given dose of >15 g/m 2 MTX as CSF levels plateau at this dose.